Comparison of maternal serum CA-125 and ultrasonography findings as a prognostic marker in threatened abortion - Yadav, Kamlesh; Ojha, Pragya; Chopra, Anant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: WHO defines abortion as pregnancy termination before 20 week gestation or with fetus born weighing <500 gms. Early pregnancy markers in patients with threatened abortion including biochemical marker like raised maternal serum CA-125 (cancer antigen-125, carcinoma antigen 125 or carbohydrate antigen 125) and USG parameters that is, fetal crown-rump length (CRL), the presence/absence of sub-chorionic hematoma and fetal heart rate (FHR) are good predictors of outcome. Methods: The study was conducted in the department of obstetrics and gynaecology, S.P. medical college and associated group of hospital, Bikaner, Rajasthan. This was a hospital based prospective comparative study. The study group comprise of pregnant females attending obstetrics and gynaecology OPD. A total of 200 pregnant women were examined in this study. We divided these patients into 2 groups, group A and group B. Group A consists of 100 pregnant females with threatened abortion and group B with 100 normal pregnant female. Results: Maternal serum CA-125 at cut off level 61.64 U/ml is 84.21% sensitive, 96.77% specific in predicting abortion with 94.12% positive predictive value and 90.91% negative predictive value while FHR at 115 bpm is 76.32% sensitive, 90.32% specific in predicting abortion with 82.86% PPV and 86.15% negative predictive value. Conclusions: Single raised value of maternal serum CA-125 has best predictive value followed by USG parameters (FHR, sub-chorionic hematoma and CRL ) in threatened abortion which results in loss of pregnancy.